Epidemiology of Animal Bites and Factors Associated With Delays in Initiating Post-exposure Prophylaxis for Rabies Prevention Among Animal Bite Cases: A Population-based Study - Esmaeilzadeh, Firooz; Rajabi, Abdolhalim; Vahedi, Sajad; Shamsadiny, Mohammad; Ghelichi Ghojogh, Mousa; Hatam, Nahid (Journal of preventive medicine and public health, 2017)
One way to prevent deaths due to rabies is the timely utilization of post-exposure prophylaxis (PEP). Therefore, in addition to an understanding of the epidemiological distribution of animal bites, it is necessary to explore the factors leading to delays in PEP initiation. This cross-sectional study was conducted in Iran in 2011, and included 7097 cases of animal bites recorded at the Rabies Treatment Center of the Shiraz University of Medical Sciences using the census method. Logistic regression was used to identify factors associated with delays in PEP. Among the patients studied, 5387 (75.9%) were males. The prevalence of animal bites in Fars province was 154.4 per 100 000 people. Dogs were the most frequent source of exposure (67.1%), and the most common bitten part of the body was the hands (45.5%). A delay in the initiation of PEP was found among 6.8% of the studied subjects. This delay was more likely in housewives (odds ratio [OR], 4.66; 95% confidence interval [CI], 2.12 to 10.23) and less likely in people with deep wounds (OR, 0.65; 95% CI, 0.43 to 0.97). Although all animal bite victims received complete PEP, in some cases, there were delays. Further, the type of animal involved, the depth of the bite, and the patient's occupation were the major factors associated with a delay in the initiation of PEP for rabies prevention.